Application of Visual Guidance Design of Tourist City Combined with Deep Learning Computer Visual Symbols. (9th September 2022) - Cai, Jiaying; Liu, Kai
Abstract : In recent years, computer vision has received rapid attention and development, and it also represents the most cutting-edge research direction of deep learning. With the rapid development of today's world economy, the arrival of the information age marked by the network has broken the boundaries of time and space in the sense of physics, and the social form in which the entire human being lives is more and more approaching a small "global village." The design and application of visual symbols need to achieve innovative combination and deconstruction of image symbols, indicator symbols, and symbolic symbols. When applying visual symbols to the design of urban tourism image, designers need to be clear about its role. The design and application of visual symbols of urban tourism image are of great significance, whether it is to condense and spread urban culture or beautify the environment. City brand image building can effectively protect the natural landscape and reduce the damage to the environment, and some city brand images can also become city landmarks. Therefore, designers should give full play to the advantages of local traditional culture, refine rich design materials, and skillfully integrate them into the design of visual symbols to further display the local humanistic characteristics, especially maximize the advantages and value of visual symbols, so as to make tourism. The city shows unique charm and unique humanistic spirit.